Optimization of Environmental Conditions for Hydroponics Using Light and Temperature Sensors Based on IoT - Ariani Amri; Baso Amir; Thitin Binalopa (Jurusan Pendidikan Teknik Elektro, 2025)
Precise environmental regulation is a critical component of hydroponic systems, particularly in urban agriculture, where land availability and resources are limited. This study aimed to examine the impact of an Internet of Things (IoT)-based hydroponic system with automated control of light intensity and temperature on the growth of Lactuca sativa (lettuce). A controlled experimental design was employed, involving 30 lettuce plants divided into control and experimental groups. Both groups were cultivated using a Nutrient Film Technique (NFT) system within a mini greenhouse over three weeks. Environmental parameters were recorded at 30-minute intervals using calibrated sensors, and plant growth was assessed by measuring stem height and leaf number. The results indicated growth increases of 52.44% in stem height and 48.89% in leaf count in the experimental group, suggesting that automated regulation of light and temperature contributes to a more stable growing environment and enhanced plant development. Nevertheless, this study is limited by its relatively short observation period and restricted range of growth indicators evaluated. Further investigations with extended experimental durations and more comprehensive growth parameters are required to assess the long-term effectiveness of IoT-based hydroponic systems.